Incidental Microscopic Granulosa Cell Proliferations: Tumorlet or Non-neoplastic?. (March 2020) - Menon, Preethi D.; Valente, Philip; Nazarullah, Alia
Abstract : Microscopic granulosa cell proliferations are rare incidental findings in ovarian and extraovarian tissue, and can simulate granulosa cell tumors. We report a case of a 22-yr-old nulliparous woman with incidental microscopic granulosa cell proliferation in the wall of an endometriotic cyst. Excision of the cyst revealed extensive endometriosis and incidental microscopic nests and cords of granulosa cells measuring 1.5 mm and positive for inhibin A and calretinin. A rare Call-Exner body was noted. An extensive literature review of both ovarian and extraovarian granulosa cell proliferations were performed to determine their possible origin, variable morphologic features and differential diagnosis. Forty-seven cases were identified occurring in pregnant (26%) and nonpregnant (74%) settings. The nonpregnant cases reveal an association with endometriosis and endometrioid adenocarcinomas. Follow-up data is very limited, but no reports of subsequent granulosa cell tumors are reported. We hypothesize that possible anovulation may play a role in the development of these proliferations. Because of unknown pathogenesis and limited follow-up data being available, their clinical significance and risk of neoplasia remain unclear.